Exploring the mechanism of border effect on urban land expansion: A case study of Beijing-Tianjin-Hebei region in China. (March 2020) - Wang, Chenglong; Liu, Hui; Zhang, Mengtian
Highlights: The administrative border has an indirect effect on urban land expansion. Border effect consists of the influence of borders on the medium and the impact of the medium on urban land expansion. Border effect is mainly caused by the influence of administrative borders on the medium. The disparity in border effect is determined by the impact of medium on urban land expansion. Abstract: Though previous studies have revealed the mechanism of urban land expansion based on different perspectives, the role of the administrative border tends to be ignored. Combined with empirical study and theoretical analysis, this paper attempts to explore the mechanism of border effect on urban land expansion. Firstly, we propose three hypotheses and develop an initial model. Then, Structural Equation Modeling (SEM) is applied to the empirical study. Based on the findings in the case study, we concretize the border effect and reveal the mechanism from a theoretical perspective. Our research indicates that borders have an indirect effect on urban land expansion. The indirect effect consists of the influence of administrative borders on medium and the impact of the medium on urban land expansion. The border effect is mainly caused by the influence of administrative borders on medium, while the disparity in border effect among cities and different years is determined by the impact of the medium on urban land expansion. Between 1990 and 2010, financial expenditure and the non-agricultural population were dominant components of the medium in the Beijing-Tianjin-Hebei region (BTHR). The social fixed asset was an important medium when regional marketization and integration were at a low level. Although urban land expands in the limited space built by administrative borders, it is caused by cross-border communication among cities. Findings in the paper are expected to enrich our knowledge of the relationship between borders and urban land expansion and provide potential support for the delineation of Urban Growth Boundary.